2020
DOI: 10.4274/meandros.galenos.2019.54376
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Traumatic Bone Cyst of the Jaws: A Retrospective Study

Abstract: Öz Amaç: Travmatik kemik kistleri (TKK) çenelerde nadir görülür ve epitelsiz bir kemik kavitesi şeklinde karakterize edilebilir. Klinik olarak, TKK asemptomatiktir ve sıklıkla rutin radyografik incelemede rastlantısal olarak bulunur. Bu çalışmanın amacı, TKK'lerin klinik, cerrahi ve radyografik özelliklerini tanımlamaktır. Gereç ve Yöntemler: Kliniğimizde 2006 ve 2016 yılları arasında kistik lezyonları olan hastaların kayıtları incelendi. Tüm odontojenik/nonodontojenik kistler arasında yirmi iki TKK tespit edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…13 ). 19 Bimaxillary SBC case (two -intramandibular cysts and one -intramaxillary cyst) of Saldaña et al macroscopically revealed samples of liquid content, bone tissue and cavity membranes, and microscopically -fibro-cellular wall with highly vascularized areas, multi-nucleated giant cells mainly in areas of hemorrhage. 14 Xanthinaki et al inside the cavity of the intramandibular SBC have found only extremely thin layer of connecting tissue and only in some places.…”
Section: Discussionmentioning
confidence: 99%
“…13 ). 19 Bimaxillary SBC case (two -intramandibular cysts and one -intramaxillary cyst) of Saldaña et al macroscopically revealed samples of liquid content, bone tissue and cavity membranes, and microscopically -fibro-cellular wall with highly vascularized areas, multi-nucleated giant cells mainly in areas of hemorrhage. 14 Xanthinaki et al inside the cavity of the intramandibular SBC have found only extremely thin layer of connecting tissue and only in some places.…”
Section: Discussionmentioning
confidence: 99%
“…SBCs is a rare clinical entity reaching only 1.05 percent among all jaw cysts. 19 Multilocular type of SBCs is even more rare and counts from 6.38 to 26.92 percent of total number of SBCs. 20,21 Already published multichamber variants of SBCs showed that the single-chamber bone cyst term cannot be applied to all SBCs as the published data and our case are proving the existence of two types of SBCs -uni-and multilocular.…”
Section: Discussionmentioning
confidence: 99%
“…osseous-like tissue (n = 3 [13.6 percent]). 19 Bimaxillary SBC case (two -intramandibular cysts and one -intramaxillary cyst) of Saldaña et al macroscopically revealed samples of liquid content, bone tissue and cavity membranes, and microscopically -fibro-cellular wall with highly vascularized areas, multi-nucleated giant cells mainly in areas of hemorrhage. 14 Xanthinaki et al inside the cavity of the intramandibular SBC have found only extremely thin layer of connecting tissue and only in some places.…”
Section: Simple Bone Cyst Of the Mandible: Histopathologic Appearancementioning
confidence: 99%